(untitled) (Experimental biology, 2025)
The sustainability of industrial poultry farming depends on the implementation of scientific and production-based biosafety strategies at the poultry farm. Objective: to assess the bacterial safety of technological matrices at a poultry farm in Kazakhstan. The research aimed at evaluating the farm’s resistance to bacterial pathogens such as Salmonella spp., Staphylococcus spp., and coliform bacteria, and was carried out in two stages: scientific-production (sample collection via surface swabs from walls and floors, equipment, and personnel) and scientific-laboratory (bacteriological analysis using cultural and biochemical methods). In total, 955 swab samples were collected from all industrial sites to assess the resistance of the farm’s technological matrices to the studied pathogens, including 336 samples from walls and floors, 485 from equipment, and 134 from the hands and uniforms of poultry workers. To assess the safety of technological matrices: 955 samples were tested for Salmonella spp., 458 for Staphylococcus spp., and 462 for coliform bacteria. Salmonella spp. was not detected. Staphylococcus spp. was isolated in October from 40 samples collected from equipment (33 samples) and rearing stock houses (7 samples), and in November from one sample taken from the feed bin in a parent stock house. Coliform bacteria were isolated in October from one sample taken from the wall of a parent stock feed truck. After pathogen detection, the farm revised its bacterial safety strategies. This is confirmed by the results of swab samples collected in the month following the positive findings: in November and December, results for Staphylococcus spp. and coliform bacteria, respectively, were negative. Thus, the general principles of bacterial pathogen control at the studied poultry farm include four scientific-production stages: development of a comprehensive biosafety program, prevention of pathogen introduction to the farm, detection of bacterial pathogens on the farm, and elimination of bacterial pathogens.